1996
DOI: 10.1002/j.1537-2197.1996.tb12748.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed hydration memory in Sonoran Desert cacti and its ecological implication

Abstract: Cactus seeds on the soil surface in the desert are subjected to periods of drought that last for up to a few months, and thus they are typically under discontinuous hydration (or discontinuous dehydration). Apparently, they can tolerate long periods of dehydration after single or multiple hydration events and subsequently germinate in accordance with the previous hydration experience. This was verified in three cactus species from the Sonoran Desert. Seeds of Stenocereus thurberi hydrated for 72 or 80 h follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0
5

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 29 publications
3
50
0
5
Order By: Relevance
“…The MGT was thus significantly reduced after HD treatment (P , 0.05 Student's t-test, Fig. 1B) as previously observed in this species (Dubrovsky, 1996). Based on these data, we concluded that in the present work we had successfully reproduced the hydration memory phenomenon.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The MGT was thus significantly reduced after HD treatment (P , 0.05 Student's t-test, Fig. 1B) as previously observed in this species (Dubrovsky, 1996). Based on these data, we concluded that in the present work we had successfully reproduced the hydration memory phenomenon.…”
Section: Resultssupporting
confidence: 89%
“…Previously, we have successfully reproduced this phenomenon by germinating F. peninsulae seeds; we observed that the germination time was dramatically reduced after an HD cycle, as expected (Dubrovsky, 1996(Dubrovsky, , 1998. As an initial approach to describing the molecular events that lead up to the enhanced germination after an HD cycle, we aimed to investigate whether there was differential expression of total proteins of seeds and seedlings subjected to the HD cycle.…”
Section: Introductionmentioning
confidence: 83%
“…The erratic precipitation at the beginning of the rainy season in 1999, the consequent damping and drying of soil and the time over which the seeds were exposed to such fluctuations, as well as variations in temperatures, could weaken the funicular envelope, favoring germination in the control seeds of O. tomentosa by forming a germination valve and a water channel and/or invigorating the embryo (loss of physiological dormancy, Orozco-Segovia et al, 2007). On the other hand, it has been demonstrated that permeable seeds of columnar cacti have a hydration memory that improves germination after seeds are exposed to hydration-dehydrationrehydration treatments (Dubrovsky, 1996(Dubrovsky, , 1998; when such Fig. 4.…”
Section: Discussionmentioning
confidence: 97%
“…HD cycles play an important role in the persistence and dynamics of plants in these ecosystems (Wilson & Witkowski 1998;Lima & Meiado 2017). Dubrovsky (1996Dubrovsky ( , 1998 points out that discontinuous hydration gives the seeds a high survival rate during desiccation, demonstrating that these seeds may present seed hydration memory, which preserves the characteristics resulting from previous hydration. A significant increase in germinability and germination speed and acquisition of higher tolerance of abiotic stresses are also results of HD cycles (Dubrovsky 1996;Rito et al 2009;Lima & Meiado 2017).…”
Section: Introductionmentioning
confidence: 99%